Study of utilization of antenatal care services in tribal area of Thane district - Bhaisare, Kalpalata Abhiman; Rao, Dasi H.; Khakase, Gautam Marotrao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Many health problems among pregnant women are preventable, detectable or treatable through visits to health facility before birth. This enables women to receive important services, such as tetanus vaccinations and screening and treatment for infections, as well as potentially life-saving information on warning signs during pregnancy.2 The objective of this study is to understand the current status of utilization of maternal health services in rural area by elucidating the various factors influencing the use of these services. Methods: It is a community based, cross sectional study carried out in a primary health centre in tribal area of Thane district. Results: 93% women received ANC care for 3 or more than 3 times. 73% women received recommended antenatal care. 68% women received ANC care exclusively from public health facility. Conclusions: Inspite of implementation of various programmes like Janani Suraksha Yojana, Matrutva Anudan Yojana and NRHM in the area percentage of registration during first trimester was less. There was lack of awareness and motivation in study subjects to come on their own to PHC for early registration of pregnancy. Though the coverage of ANC services was good it was not of good quality.